Analysis of Determination of Sea Toll Routes in Eastern Indonesia (KTI) Using Dynamic Programming - Regita Ernawati; Surachman Surjaatmadja; Pujo Widodo; Herlina Jr. Saragih; Panji Suwarno; Marsetio Marsetio; Surya Wiranto (Dinamika Bahari, 2023)
The sea highway program is part of the fourth pillar, namely the pillars of the maritime economy, infrastructure and increasing welfare, one of the seven pillars of Indonesia's Maritime Policy (KKI). The aim of the Sea Highway Program is to grow the maritime economy by turning the sea into a production and marketi ng center between the Indonesian territory and the islands and surrounding areas. This study aims to analyze the decision of maritime highway routes in Eastern Indonesia Region (KTI) in order to provide the best route with a minimum distance. Four shipping highway routes from Surabaya to Eastern Indonesia Region, namely route T-13 (Tanjung Perak-Rote (Ndao)-Sabu (Biu)-Tanjung Perak), T-14 (Tanjung Perak-Lembata (Lewoleba)-Tabilota/Larantuka- Tanjung Perak), T-15 (Cape Perak-Makassar (Soekarno Hatta)-Jailolo-Morotai (Daruba)-Tanjung Perak), and T-18 (Tanjung Perak-Badas-Bima-Merauke (Kelapa Lima)-Tanjung Perak) combined into 1 (one) route from Tanjung Perak to Merauke, resulting in 1 (one) optimal route with the minimum distance obtained from the smallest value at each stage . This study uses quantitative methods and Multistage Graph problem-solving techniques with Dynamic Programming backward or bottom-up methods, and primary data collection through interviews and secondary data such as: documents/journals/books. The selected optimal route is (Tanjung Perak-Makassar-Tabilota/Larantuka-Sabu (Biu)-Merauke (Kelapa Lima)) with a distance from Tanjung Perak to Makassar is 437 Nm. Makassar to Tabilota/Larantuka is 340 Nm. Tabilota/Larantuka to Sabu (Biu) is 163.8 Nm. Sabu (Biu) to Merauke (Kelapa Lima) is 1261.24 Nm. So that the total shipping distance from Tanjung Perak to Merauke is 2202.04 Nm.